a)
[tex](\frac{1}{2} \sqrt[3]{12} )^3 = \frac{1}{2}*\frac{1}{2}*\frac{1}{2}*12=\frac{1}{8}*12=\frac{1}{8}*\frac{12}{1} =\frac{1}{2}*\frac{3}{1}=\frac{3}{2}=1\frac{1}{2}[/tex]
b)
[tex](-2\sqrt[3]{\frac{1}{4}})^3=-2*-2*-2*\frac{1}{4}}=-8*\frac{1}{4}}=-\frac{8}{1}*\frac{1}{4}}=-\frac{2}{1}*\frac{1}{1}}=-2[/tex]
c)
[tex](-10\sqrt[3]{-0,1} )^3=-10*-10*-10*-0,1=-10*-10=100[/tex]
d)
[tex]3\sqrt[3]{7}*2(\sqrt[3]{7})^2=3\sqrt[3]{7}*2(\sqrt[3]{7}*\sqrt[3]{7})=3\sqrt[3]{7}*2\sqrt[3]{49}=3*2*(\sqrt[3]{7} )^3=6*7=42[/tex]